Resistência de variedades de mandioca à cochonilha Phenacoccus manihoti (Matile-Ferrero) e sua influência sobre o parasitoide Anagyrus lopezi (De Santis) - Rheinheimer, Ana Raquel (2013)
Phenacoccus manihoti is an important pest of cassava in the region Center-South of Brazil, causing damage mainly cultivated during the second cycle. The use of resistant genotypes and biological control agents are the most promising techniques in the control of this pest. The objective of this research was to evaluate the resistance of genotypes of cultivated cassava and obtained in breeding programs to mealybug P. manihoti and its influence on the parasitoid A. lopezi. The biological aspects of P. manihoti and A. lopezi were evaluated in different cassava genotypes and with these data tables of life and fertility of both were prepared. To verify the occurrence of resistance induction of infestation of P. manihoti genotypes were evaluated on the activity of peroxidase, polyphenol oxidase , amino acids and reducing sugars . In the absence of mealybug was also rated the content (CN-) of different genotypes. Although P. manihoti and A. lopezi showed differences in their biological aspects when reared on different genotypes of cassava has not been possible to verify the action of resistance of genotypes evaluated on these parameters. There was a positive correlation between fecundity of A. lopezi and its host P. manihoti in different genotypes, indicating that genotypes susceptible to mealybug positively influence the reproduction of its parasitoid . We observed an increased incidence of plant defenses due to inoculation with P. manihoti associated with increases in the activity of peroxidase, polyphenol oxidase, amino acids and reducing sugars in most genotypes. However, only the activities of peroxidase and polyphenol oxidase appear to be involved in the resistance of the genotypes evaluated